Perancangan UI/UX Aplikasi Buku Online Mizanstore Berbasis Mobile Menggunakan User Centered Design - Muhammad Hafizh Hamdanuddinsyah; Mukhtar Hanafi; Pristi Sukmasetya (Journal of Information System Research (JOSH), 2023)
Currently, e-commerce has become a crucial necessity for society as it provides convenience and comfort in shopping. MizanStore, as an e-commerce platform, enables people to search for and purchase various products they need without leaving their homes. In this ever-evolving era, the use of mobile platforms is preferred over websites due to advantages such as easy accessibility and better user experience. Hence, a research study was conducted to design optimal user interface (UI) and user experience (UX) through the development of the MizanStore mobile application. The User Centered Design (UCD) methodology was implemented in this research, involving four main stages. These stages encompassed understanding the application's usability, conducting in-depth analysis of user needs, developing responsive design solutions, and evaluating through continuous testing. By employing this approach, existing issues were identified and addressed, resulting in a prototype design model that aligns with user expectations and desires. Testing was conducted with the participation of 10 users, utilizing the System Usability Scale (SUS) questionnaire. The results indicated that MizanStore obtained an average SUS score of 90, demonstrating high user satisfaction and alignment between the application and their needs. These findings provide a solid foundation for further improvement and development of MizanStore. Consequently, MizanStore can continue to deliver an optimal shopping experience and better meet user needs.